Assessment of sustainability of oil palm cultivation for smallholder farmers of Mizoram - Zomaunpuii, Nancy; Loukham Devarani (Umiam: CPGSAS, CAU(Imphal), 2024)
Oil palm is one of the most efficient and widely used vegetable oils yielding plant. It gives the highest yield of edible oil per hectare of crop as compared to the present yields from all other oil crops. In view of the rising significance and need of oil palm in India, the Government of India has been supporting the area expansion and output increase of oil palm. Mizoram is the pioneering State in NE Region to take up oil palm cultivation on large-scale, commencing in 1999-2000 and expanded to promote stable livelihoods and replace shifting cultivation practices. However, the farmers perceived it as not dependable or hardly dependable for meeting livelihood requirements. There are reports of many growers, especially the smallholders discontinuing the cultivation of the crop, questioning the sustainability of oil palm cultivation. With this backdrop, the present study was conducted to assess the sustainability of oil palm cultivation for smallholder farmers of Mizoram with the following objectives i) To assess the sustainability of oil palm cultivation for smallholder farmers ii) To study the challenges of smallholder farmers in oil palm cultivation. This study adopted a survey with mixed methods. The locale of the study was Kolasib district, Mizoram. A total of 84 respondent farmers were selected with complete enumeration for the relevant data. The data collection was done using pre-tested structured interview-schedule. The collected data was analysed employing suitable descriptive and inferential statistics using SPSS tool. The study constructs a composite index using multi-variate analysis of Principal Component Analysis (PCA), the results show that from the identified 3 dimensions, the environmental dimension retain 6 indicators, the economic dimension retain 5 indicators and the social dimension retain 11 indicators. After computation of the weightage, the social dimension was found to have the highest mean score (0.38) followed by the economic dimension (0.33) and lastly the environmental dimension (0.29). Further, the study stated the challenges faced by the smallholder farmers. Prioritization should be given on the challenges of poor road infrastructure, inadequate and generalised training and advisory support, lack of fertile soil as well as existence of competition in alternate cash crop. The study is based on three dimensions of sustainability, in which the water management, productivity and poverty level from each dimension has contributed the least in sustainability. Based on the findings, this study recommends promotion of adoption of effective methods and techniques among the farmers for water harvesting and provision of regular training and skills development of the farmers related to field operation. and improvement of the infrastructure for improving accessibility to the collection centres.
Keywords: Oil palm -- Cultivation -- Mizoram; Oil palm -- Sustainability; Smallholder farmers -- Sustainability